An investigation into the Socio-linguistic features of english loanwords used in vietnamese newspapers published In the 2000s (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This is essentially the investigation of the socio-linguistic features of English loanwords used in Vietnamese newspapers published in the 2000s. The socio-political-cultural reasons for the appearance of English loanwords in Vietnamese newspapers published in the 2000s are identified. A corpus for 426 samples of English loanwords collected from different kinds of Vietnamese newspaper published in the 2000s is analyzed to examine the loanword adaptations at three perspectives: phonetic, grammatical and semantic features. This study also analyses the readers’ attitudes towards the use of English loanwords by Vietnamese journalists and the controversial views about the English loanwords in Vietnamese language system. Finally, the study also predicts potential problems and puts forwards some suggestions for language teaching.